"I think they believe in me": The predictive effects of teammate- and classmate-focused relation-inferred self-efficacy in sport and physical activity settings - Jackson, B.; Gucciardi, Daniel; Lonsdale, C.; Whipp, P.; Dimmock, J. (Human Kinetics, 2014)
Despite the prevalence of group-/team-based enactment within sport and physical activity settings, to this point the study of relation-inferred self-efficacy (RISE) has been focused upon estimations regarding a single target individual (e.g., one’s coach). Accordingly, researchers have not yet considered whether individuals may also form RISE estimations regarding the extent to which the others in their group/team as a whole are confident in their ability. We applied structural equation modeling analyses with cross-sectional and prospective data collected from members of interdependent sport teams (Studies 1 and 2) and undergraduate physical activity classes (Studies 3 and 4), with the purpose of exploring these group-focused RISE inferences. Analyses showed that group-focused RISE perceptions (a) predicted individuals’ confidence in their own ability, (b) were empirically distinct from conceptually related constructs, and (c) directly and/or indirectly predicted a range of downstream outcomes over and above the effects of other efficacy perceptions. Taken together, these findingsprovide preliminary evidence that individuals’ group-focused RISE appraisals may be important to consider when investigating the network of efficacy perceptions that develops in group-based physical activity contexts.